The role of general practitioners in the management of erectile dysfunction - a qualitative study - Ng, C.J.; Low, W.Y.; Tan, N.C.; Choo, W.Y. (2004)
The objective of this study was to explore the roles and perceptions of general practitioners (GPs) in the management of erectile dysfunction (ED). This qualitative study used focus group discussions and in-depth interviews. This study was conducted based on 28 GPs from an urban area in Malaysia who had managed patients with ED and prescribed anti-ED drugs. Main outcome measures included the roles of GPs in managing patients with ED ( active or passive), perceptions regarding ED and the treatment, and factors influencing their decision to prescribe. Majority of the GPs assumed a passive role when managing patients with ED. This was partly due to their perception of the disease being nonserious. Some also perceived ED as mainly psychological in nature. The anti-ED drugs were often viewed as a lifestyle drug with potentially serious side effects. The fear of being perceived by patients as 'pushing' for the drug and being blamed if the patients were to develop serious side effects also hampered the management of this disease. GPs who participated in this study remained passive in identifying and treating patients with ED and this was attributed to their perception of the disease, drug treatment and patient's background.